Nalar Moderasi Tafsir Pop Gus Baha' - Fathurrosyid Fathurrosyid (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
Abstract The new media revolution has given the freedom to the religious authority (Islam), both the old authority and the new one to contest to win the hearts of the people. The fact is that the public sphere is being controlled by the new religious authority with a radical and intolerant face of Islam. Apart from the government and educational institutions, the effort to dispel extremism through counter narratives are also carried out by civil society by campaigning Islamic moderation. This article discusses the dissemination of the moderation reasoning of the Pop Tafsir of Gus Baha’ on YouTube. The focus of this article is on the aspect of contestation to the new authority as an effort to deradicalize the interpretation. Using virtual ethnographic data, this paper draws conclusions. First, the dissemination of the miracle reconstruction of the Qur’an and argumentative logic in preaching. Second, the dissemination of the urgency of the nasikh-mansukh as a critic of the kaffah Islamic movement and as the priority of moderation reasoning in the loyal attitude to maintain the integrity of the Republic of Indonesia from the threat of separatism. Third, disseminating counter-narratives that use God’s status to dispel extremism and radicalism Keywords: Contestation, Gus Baha’, Moderation Reasoning, Pop Tafsīr.